Monitoring the Process of Endostar-Induced Tumor Vascular Normalization by Non-contrast Intravoxel Incoherent Motion Diffusion-Weighted MRI - Pan, Jing-hua; Zhu, Shengbin; Huang, Jinlian; Liang, Jianye; Zhang, Dong; Zhao, Xiaoxu; Ding, Hui; Qin, Li; Shi, Changzheng; Luo, Liangping; Pan, Yunlong (Frontiers in Oncology, 2018)
Tumor vascular normalization has been proposed as a new concept in anti-tumor angiogenesis, and the normalization window is considered as an opportunity to increase the effect of chemoradiotherapy. However, there is still a lack of a noninvasive method for monitoring the process of tumor vascular normalization. Intravoxel incoherent motion diffusion-weighted magnetic resonance imaging (IVIM DW-MRI) is an emerging approach which can effectively assess microperfusion in tumors, without the need for exogenous contrast agents. However, its role in monitoring tumor vascular normalization still needs further study. In this study, we established a tumor vascular normalization model of CT26 colon-carcinoma-bearing mice by means of Endostar treatment. We then employed IVIM DW-MRI and immunofluorescence to detect the process of tumor vascular normalization at different times after treatment. We found that the D* values of the Endostar group were significantly higher than those of the control group on days 4, 6, 8, and 10 after treatment, and the f values of the Endostar group were significantly higher than those of the control group on days 6 and 8. Furthermore, we confirmed through analysis of histologic parameters that Endostar treatment induced the CT26 tumor vascular normalization window starting from day 4 after treatment, and this window lasted for 6 days. Moreover, we found that D* and f values were well correlated with pericyte coverage (r=0.469 and 0.504, respectively; P<0.001, both) and relative perfusion (r=0.424 and 0.457, respectively; P<0.001, both). Taken together, our findings suggest that IVIM DW-MRI has the potential to serve as a noninvasive approach for monitoring Endostar-induced tumor vascular normalization.